Forms and Factors Affecting Collective Adaptation to Saline Intrusion: A case of Kien Giang Province, Vietnam - Cam Thi Hong Nguyen; Van Huynh Thanh Pham; Rudi Febriamansyah (International Journal of Agricultural Sciences, 2019)
Saline intrusion (SI) is causing serious risks for agriculture and coastal life in the Vietnamese Mekong Delta. Maintaining agricultural production under that challenging condition places more tremendous pressure on rural societies. This study aimed to get insight into adaptive adaptation's forms and factors influencing farmers' participation process by applying the social and ecological approach. The research was conducted in An Bien district, Kien Giang province, a province in the Mekong Delta in Vietnam. A mixed-method integrating quantitative and qualitative methods were used to collect data using key informant panel interviews, group discussion, and household survey. The results showed that local farmers had changed the farming system from double rice crops to shrimp-rice models to deal with the impacts of SI. Group response has emerged as the appropriate adaption in both formal and informal forms. The adaptive group plays an essential role in connecting community members, and two forms of adaptation have worked closely to adapt to SI. Factors affecting the informal group related to relatives, households living close to each other; For the formal group, the main factor affecting participation is when joining the group, the members receive benefits from the group. Besides, prestige and having a lot of experience in the leader's production activities affect the official group participation. In addition to the positive factors, two negative factors affect group adaptation: unfavorable farm location and distrust